The Effectiveness of Growth Mindset-Based Role Play in Improving Early Childhood Self-Confidence - Mutmaina Hani; Durrotunnisa Durrotunnisa; Sita Awalunisah; Andi Agusniantih; Razkia Razkia; Vita Marcella; Agis Agis (Journal of Education Research, 2026)
This study aims to determine the effectiveness of the role-playing method based on a growth mindset in improving early childhood self-confidence in Group A of TK Kemala Bhayangkari 16 Palu. This research employed a quasi-experimental approach with a one-group pretest-posttest design. The subjects of this study were 14 children aged 4–5 years. Data were collected through observation based on three indicators: courage to perform and participate, ability to express opinions, and independence and perseverance. The results showed that in the pretest phase, most children were in the "Beginning to Develop" and "Not Yet Developed" categories. After the treatment was given, the posttest results indicated a significant improvement, with most children reaching the "Developing as Expected" and "Very Well Developed" categories. Statistical analysis using a paired sample t-test showed a significance value of 0.000 < 0.05, indicating a significant difference between pretest and posttest results. Thus, it can be concluded that the role-playing method based on a growth mindset is effective in improving early childhood self-confidence.